(untitled) (Journal of the College of Basic Education, 2022)
The research aims to analyze the middle/second grade math book according to/productive thinking skills,The descriptive-analytical approach was use. There search sample consisted of amathematics book for these condintermediate grade,which was established by the Iraqi Ministry of Education,the General of Directorate Curriculaforthe academic year(2021-2022AD),initsfirst/second parts, For this purpose , I have prepared an analysistool represented in the list of productive thinking skills, Its validity was verified by presenting it to a group of specialists in curricula and teaching methods, The idea unit (implicit and explicit idea) is adopted as the recording unit, and the frequency as the enumeration unit, The validity of the analysis was also verifiedbyapresentation Holist Asample of the Analysis on a group of arbitrators,/used/frequencies and percentages/and an equation To calculate the stability of the analysis between the researcher and herself over time and between her/and other analysts,Theresults showed that the productive thinking skills were distributed unbalancedly and in varying and clear proportions, where the induction skill ranked first with a rate of (21.5%), the skill of predicting assumptions ranked second at a rate of (18.3%)/,and the skill of evaluating discussions ranked third with a rate of (16.5%), and the skill of predicting assumptions ranked second with a rate of (18.3%) , and the skill of evaluating discussions rankedthird witharate of (16.5%), andtheThe fourth was gained by the fluency skillat arate of (14.5%),respectively,while the leastin clusive percentages werefrom theshare of my creative thinking skills (originality ranked last (seventh) at arate of(5.4%),andflexibility got the rank Sixth (10.5%). According to these results ,many recommendations were presented, including the necessity of including productive thinking skills in the mathe matics book of the second grade inter mediatelevel in abalanced andregular manner with/taking into account the sub-skills /productive thinking ,especially the skills that are less included in the mathematics book of the second intermediate grade/,as well as, Anumber of proposals were also presented as conducting more studies to identify the availability ofthe restof the textbooks for productive thinking skills that are not/specific to aspecific subject, but must/be developed/in/all curricula/and conduct a comparative analytical study /between the mathematics booksof the preparatory stage in Iraq and one of the Arab countries/in/the light of/skills/thinking/product